Trace elements and nutrients in white poplar trees affected by the Aznalcóllar mine spill - Madejón, P. (Forest Systems, 2003)
Nutrient and trace element concentrations in leaves and branches of poplar (Populus alba L.) have been studied two years after the Aznalcóllar mine spill. The soils of the Guadiamar channel (where poplar was sampled) were still greatly polluted by trace elements, due in part to the difficulty for cleaning up these particular sites. However, nutrient contents (N, P, K, Ca and Mg) of the plants were not affected by the soil pollution. Sulphur content was high in the affected trees, however, the concentrations were not toxic for the physiology of the plant. In general, As, Cd, Pb and Tl contents were in the normal range for plants and did not reach phytotoxic levels. Only Zn could be somewhat excessive for some particular trees. Although trace element contents do not seem to be worrying for white poplar, a continuous monitorization is advisable.